Transformasi Misi Diera Digital: Tantangan Dan Peluang - Paraeng, Resdiana (PT. Giat Konseling Nusantara, 2025)
In the past 10 years, digital technology has changed many aspects of life, including how churches and religious organizations carry out their mission. Today, many activities like worship, learning, and service are done online. This study aims to understand how mission works in the digital era and what challenges and opportunities come with it. The method used is descriptive qualitative, by reading books and journals, observing online mission activities, and conducting interviews. The results show that digital mission can reach more people, but also faces challenges such as ethics, digital culture, and technology. Therefore, churches need a wise and relevant approach to keep their mission effective in the digital world.